Practices in social media in the travel education business - Verstraeten, Jean-Benoit Pierre Joel Vincent (2015)
Practices in Social media refers to the view or perception of a brand not only based on its offerings and services, but also on its values and culture as perceived primarily by consumers. Organizations may utilize brand image to accomplish its goals or objectives by structuring an image that is interesting and acceptable to customers. In recent years, one of the ways that organizations consistently market or advertise their brand involves social media. The objective of this research study is to explore what are the practices in social media in the travel education business. To obtain data, the researcher interviewed people from 6 travel education firms and collated information about the topic from existing primary and secondary sources. The researcher conducted the research to determine practices in social media marketing as they apply in the tourism and education sectors. Based on the data obtained by the researcher, practices in social media marketing include the utilization of social media platforms with a widespread international reach such as Facebook, Twitter, Instagram, and YouTube. Another strategy is to constantly post updates that are not only interesting but also informational about the products and services offered by a brand or organisation. Companies or organizations must also interact with customers or clients online in order to maintain the latter’s interests in the former’s offerings and services. Customer engagement is one of the reasons why customers opt to follow firms online through social media. The research study also reveals other advantages and benefits of social media that constitute best practices such as the conversion of non-customers to customers, increased media presence to boost popularity, the effective communication of organisational goals and objectives, and the formation of a good relationship with customers. Organisations may also use tourist created content (TCC) and other types of user-generated content to guide decision-making in product development.